Gestión presupuestaria en la papelería e imprenta el Copión de la ciudad de Babahoyo. - Anchundia Vera, Dulce Alejandra (2022)
The present case study deals with the budget management in the stationery and printing press of the city of Babahoyo, where the objective is to know the budget management of the enterprise, which allowed us to see the inconveniences that are presented day by day, from the loss of materials that you had during the time of confinement due to the COVID-19 pandemic to the purchase of low-selling products, in order to provide alternatives for improvements in your budget so that you can recover sales, improve customer service and be able to Have efficient inventory management. For the respective investigation, several methods were carried out, such as direct observation and the interview with the owner of the establishment, where it was possible to conclude that many of the inconveniences that the company presents are due to the lack of inventory and the management of the budget in an incorrect way. the despair of being able to recover sales and the store not go bankrupt, so he did not realize the losses he was causing, generating staff layoffs and salary reductions.